Pengaruh Current Ratio Dan Debt To Equity Ratio Terhadap Return On Equity Pada PT Industri Jamu Dan Farmasi Sido Muncul Tbk Periode 2015–2024 - Aan Hermawati; Intan Sari Budhiarjo (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to examine the effect of the Current Ratio and Debt to Equity Ratio on Return on Equity at PT Industri Jamu and Farmasi Sido Muncul Tbk during the period 2015–2024, both partially and simultaneously. The research method employed is quantitative. The data used are secondary data in the form of financial statements of PT Industri Jamu and Farmasi Sido Muncul Tbk over a ten-year period from 2015 to 2024, obtained from the company’s annual financial reports. The analytical methods applied include financial ratio analysis, descriptive statistical analysis, multiple linear regression analysis, classical assumption tests, hypothesis testing, and coefficient of determination analysis using SPSS software. The results of the study indicate that partially, the Current Ratio (X₁) does not have a significant effect on Return on Equity (Y), as shown by the t-test results where tcount < ttable (0.540 < 2.306) with a significance value of 0.606 > 0.05. Partially, the Debt to Equity Ratio (X₂) also does not have a significant effect on Return on Equity (Y), as indicated by tcount < ttable (0.448 < 2.306) with a significance value of 0.668 > 0.05. However, simultaneously, the Current Ratio (X₁) and Debt to Equity Ratio (X₂) have a significant effect on Return on Equity (Y). This is evidenced by the F-test results showing Fcount > Ftable (6.225 > 4.74) with a significance value of 0.028 < 0.05, therefore, the alternative hypothesis Hₐ is accepted and the null hypothesis H₀ is rejected.